The Finite Spectrum of Fourth-Order Boundary Value Problems with Transmission Conditions - Fang-zhen Bo; Ji-jun Ao (Abstract and Applied Analysis)
A class of fourth-order boundary value problems with transmission conditions are investigated. By constructing we prove that these class of fourth order problems consist of finite number of eigenvalues. Further, we show that the number of eigenvalues depend on the order of the equation, partition of the domain interval, and the boundary conditions (including the transmission conditions) given.